Meningkatkan Kepercayaan Diri dalam Menyampaikan Pendapat melalui Layanan Bimbingan Kelompok pada Siswa Kelas II SDN 105367 Desa Karang Anyar - Syarqawi, Ahmad; Rambe, Afghan Bai Asy Ary; Tanjung, Asbih Fahrezi; Rezeki, Leni Sri; Dewi, Suharti Neng (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The research aims to find out the results of implementing group counseling services to improve self-confidence in students at SDN 105367 Desa Karang Anyar. The research was conducted using a descriptive research method with a qualitative approach and a case study approach. Data collection processes included observation, interviews, and documentation studies, using Miles and Huberman's analysis, which involves data reduction, data presentation, and drawing conclusions. The research subjects were students at SDN 105367 Desa Karang Anyar. The research found that the self-confidence of the second-grade students at SDN 105367 Desa Karang Anyar increased after the group counseling sessions. This was evident in the changes in attitude and behavior demonstrated by the students, who initially were more passive and quiet but became more active and confident after participating in the group counseling.